Chloride resistance penetration of rubberized-ultra-high performance concrete (UHPC) - Muhammad Hafiz, Ishak (2018)
Solid waste disposal from waste by-products are one of the major environmental issue nowadays such as tires disposal. The utilization of recycled tyre as aggregate replacement in normal concrete and high strength concrete has been explored. Nowadays, UHPC has become famous due to high compressive strength that can achieved more than 100 MPa. UHPC was produced by using low water cement ratio and replacing the ordinary Portland cement (OPC) with 10% silica fume improved significantly its workability, strength and durability. In this study, an idea to replace the amount of aggregate with waste crumb tyre (WCT) in UHPC mixture was investigated. The WCT was replaced constantly at 5% from the total weight of aggregate. The WCT particle was subjected to pre-treatment process by immersing the WCT particles in NaOH solution for 20, 40 and 60 minutes. Two (2) type of testings namely durability test and chloride penetration were conducted. For durability test, the UHPC samples were immersed in 3% NaCl solution for 7, 14 and 28 days and the exposed specimens were tested in terms of its strength and weight loss. The chloride penetration depth of exposed UHPC was also evaluated. The results showed that the compressive strength for entire rubberized-UHPC significantly lowest in strength as compared to plain UHPC. The chloride penetration depth for rubberized-UHPC was higher value as compared to plain UHPC. In the rubberized-UHPC, UHPC-20 has higher value for chloride penetration depth than UHPC-40 and UHPC-60. The results revealed that UHPC-60 enhanced the chloride resistant penetration than UHPC-20 and UHPC-40.